EMERGENT WRITING OF EARLY CHILDHOOD IN EARLY CHILDHOOD EDUCATION - Hidayati, Novi; Sulaeman, Eman; Halimatussyadiyah, Iis Siti Umi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research is motivated by differences in the pros and cons of introducing writing to children in early childhood education institutions and the encouragement from parents so that their children can have the ability to write so that it is not uncommon for teacher to be in the wrong position. This research aims to look at the readiness of children in writing skills and the introduction of writing skills in early childhood education by teacher. Descriptive qualitative is the method used in this study. The choice of this method is to provide an in-depth description and description of the introduction of writing skills in early childhood, especially in group A children aged 4 – 5 years. Participants in this study were 18 children in group A and 3 class teachers in group A. Data collection in this study used observation and interview. Interviews were conducted directly and openly with 3 class teachers. The data collected by the children was analyzed using the Clark and Braun thematic analysis technique. This study found that in the first semester in group A, they did not have the readiness to introduce writing skills so the children's teacher introduced writing skills in the second semester. There is no readiness in this child because the child's fine motor development has not developed properly, so the main focus is on the achievement target, namely on the development of children's development, especially fine motor skills. This achievement target and media are different from the previous year, this is due to the lack of habit of writing in the home environment, the role of parents, and the collaboration of teacher with parents